Hypoglossal Nerve Stimulator Placement for Pediatric Trisomy 21 Patients with Refractory Obstructive Sleep Apnea: A Case Series - Joelle B. Karlik; Nikhila Raol; Laura Gilbertson (MDPI AG, 2020)
Background: Hypoglossal nerve stimulators (HNS) are an increasingly popular form of upper airway stimulation for obstructive sleep apnea (OSA) in adults who are unable to tolerate positive pressure treatment. However, HNS use is currently limited in the pediatric population. Case presentation: We present a case series detailing the anesthetic management of three pediatric trisomy 21 patients receiving HNS for refractory obstructive sleep apnea. The patients tolerated the procedure well and experienced no complications. The average obstructive apnea-hypopnea index (AHI) change was 87.4% with the HNS. Conclusions: Proper anxiolysis, safe and controlled induction, multimodal analgesia, and minimization of post-operative respiratory compromise are all necessary to ensure anesthetic and surgical success. After a tailored anesthetic regimen, proper device placement and close follow-up, our patients had a marked improvement in obstructive symptoms.